Failure of authoritarian learning: explaining Burma/Myanmar's electoral system. Issue 3 (3rd April 2018) - Dukalskis, Alexander; Raymond, Christopher D.
ABSTRACT: What explains why some authoritarian governments fail to take all the steps they can to preserve their positions of power during democratic transitions? This article examines this question using the example of the leading pro-military party in Myanmar, which lost badly to the National League for Democracy (NLD) in the transitioning elections of 2015. This article argues that a key to understanding how the military failed to perpetuate its power in the electoral sphere resides in its choice of electoral system. In 2010, the military junta chose an electoral system, first-past-the-post, that was distinctly ill-suited to preserve its power. We explore several hypotheses for why this occurred and ultimately conclude that the military and its allies did not understand electoral systems well enough to act strategically and that they overestimated their support relative to the NLD. This failure of authoritarian learning has important implications for understanding authoritarian politics, democratic transitions, and the challenges faced by authoritarian governments seeking to make such transitions.